The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1080/15287398109530066
|View full text |Cite
|
Sign up to set email alerts
|

Early life stage toxicity tests with a saltwater fish: Effects of eight chemicals on survival, growth, and development of sheepshead minnows (cyprinodon variegatus)

Abstract: Flow-through, acute (96-h), and early life stage (28-d after hatch) toxicity tests were performed with eight chemical on a saltwater fish, sheepshead minnows (Cyprinodon variegatus). Chemical effects on survival, growth, and development were determined. Maximum acceptable toxicant concentrations (MATCs) were greater than 3.2 less than 7.7 mg/l for toluene, greater than 0.52 greater than 0.97 mg/l for acenaphthene, greater than 80 less than 156 mg/l for isophorone, greater than 10 less than 16 mg/l for 4-nitrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A literature review suggests that the levels of bromoform found in our study will not adversely affect marine organisms. Toxicity data are available for phytoplankton Skeletonema costatum, Thalassiosira pseudonana, Glenodinium halli and Isochrysis galbana (Erickson & Freeman 1978), mysid shrimp Americamysis bahia (US Environmental Protection Agency 1978), brown shrimp Penaeus aztecus (Andersen et al 1979), Atlantic menhaden Brevoortia tyrannus (Andersen et al 1979), and sheepshead minnow Cyprinodon variegates (Heitmuller et al 1981, Ward 1981. Data for these species suggest that the quantity of bromoform produced during our shipboard experiments was not acutely toxic with IC 50 (50% inhibition concentration), LC 50 (50% lethal concentration), or NOEC (no observed effect concentration) values 1 to 2 orders of magnitude higher than the quantities we observed.…”
Section: Disinfection Byproduct Chemistrymentioning
confidence: 99%
“…A literature review suggests that the levels of bromoform found in our study will not adversely affect marine organisms. Toxicity data are available for phytoplankton Skeletonema costatum, Thalassiosira pseudonana, Glenodinium halli and Isochrysis galbana (Erickson & Freeman 1978), mysid shrimp Americamysis bahia (US Environmental Protection Agency 1978), brown shrimp Penaeus aztecus (Andersen et al 1979), Atlantic menhaden Brevoortia tyrannus (Andersen et al 1979), and sheepshead minnow Cyprinodon variegates (Heitmuller et al 1981, Ward 1981. Data for these species suggest that the quantity of bromoform produced during our shipboard experiments was not acutely toxic with IC 50 (50% inhibition concentration), LC 50 (50% lethal concentration), or NOEC (no observed effect concentration) values 1 to 2 orders of magnitude higher than the quantities we observed.…”
Section: Disinfection Byproduct Chemistrymentioning
confidence: 99%
“…In contrast, both bromate ion and bromoform are substantially less toxic than bromine and, therefore, are unlikely to contribute any significant toxicity. Bromate ion LC50 values range from 30 mg/L for the Pacific oyster (Crassostrea gigas) to 512 mg/L for the chum salmon (Oncorhynchus keta) [28], and bromoform LC50 values range from 7.1 mg/L for sheepshead minnows [47] to 26 mg/L for the brown shrimp (Penaeus aztecus) [48]. In the studies onboard the S/ T Tonsina that used a ozonation system similar to that in the present study, bromate ion was never detected, and bromoform was found to occur at concentrations less than 1 mg/L [25].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have investigated the effects of waterborne PCNs to fish and QSAR models have also been developed for acute toxicity of PCN congeners to fish (Gu et al., 2021; Nath et al., 2023; Sişman & Geyikoğlu, 2008; Ward et al., 1981). Because of the high octanol–water partition coefficient ( K ow ) of PCNs, it is likely that water is not an important route of exposure (Pärt, 1989).…”
Section: Assessmentmentioning
confidence: 99%